Content Marketing Analysis of Body Positivity Campaign on Instagram: Case Study of Nipplets - Swastika, Gabriela; Audrey, Felicia; Purnomo, Felita (CHANNEL: Jurnal Komunikasi, 2022)
Women often lack confidence in their body shape. Apart from the lack of confidence, women’s bodies are also the target of humiliation and harassment, such as body shaming, especially on social media. With these problems, various organizations and business enterprises have sprung up. One of them is Nipplets, an online shop that sells lingerie. Nipplets has launched a “Real People Real Body” (RPRB) campaign to involve their customers as models to represent lingerie products. The problem formulation in this study is how to analyze the content of the RPRB campaign on the @nipplets_official Instagram account. This study aims to determine the role of the RPRB campaign in Nipplets content marketing using posts, hashtags #realpeoplerealbody, and tags or mentions. The theoretical foundations used in this study include representation, campaign theory, and social media marketing. This study used a descriptive approach within the textual analysis. The RPRB I campaign was an initiative to spread awareness of body positivity. The RPRB II campaign was considered successful in symbolizing the muse. In contrast, the RPRB III campaign was a continuation of the campaign using relevant tags consistently and in line with images and captions. The RPRB campaign trilogy by Nipplets has completed the interaction, which can be marked by customers wearing Nipplets lingerie products. The RPRB I, II, and III involvement support the marketing of Nipplets lingerie to answer the phenomenon of humiliating women’s bodies in Indonesia.